Analisis Perbandingan Upah Harian dengan Borongan (Studi Kasus Proyek Peningkatan Kualitas Permukiman Kumuh Desa Lagasa) - Lisman, Lisman; Sufrianto, Sufrianto; Hakiman, Hakiman; Ilham, Vickky Anggara (Universitas Sulawesi Tenggara, 2023)
There are several types of wage systems in a construction project, including a time-based wage system, namely providing wages based on time for work that has been carried out by craftsmen, such as daily work. There is also a piece rate wage system, which provides wages directly based on the amount of workmanship produced by the craftsman. Contractors must be careful in providing wages to workers, so that the work is in accordance with the planned time, whether the contractor benefits or not. If the work time is less or even ineffective for the journeyman, then it is certain that the contractor will suffer losses because the resulting productivity is small. Based on the analysis for the productivity of daily workers and piece workers, the productivity of piece workers is greater than that of daily workers in the work of Improving the Quality of Lagasa Village Slum Settlements. For piece work on taluds for area A it is 62.47 m3/day, while daily work on taluds for area A is 7,809 m3/day, for work on drainage for area B it is 78.15 m^1/day while daily work on drainage for area B is 9, 77 m^1/day and for wholesale block paving work in area C it is 526.65 m^2/day while daily block paving work in area C is 65.83083 m^2/day